The importance and challenges of a precise diagnosis for IPM: seeing the problem from different perspectives within the soybean-corn production system - Bueno, Adeney F.; Sutil, Weidson P.; Hoshino, Adriano; Silva, Gabriela V. (Entomological Communications, 2024)
One of the keystones for successful IPM is a precise diagnosis. Identifying and quantifying the culprit triggering the problem is crucial for making a decision based on injury level, plant tolerance, and potential strategies to mitigate losses. Recently, growers complained that crickets were damaging their soybean crops. However, after analyzing the injured fields in more detail, mice were identified as being responsible for the recorded injuries. The occurrence of crop injuries caused by mice is not restricted to soybean fields but has also been reported for corn fields. In this report, we illustrate the importance of a precise diagnosis to avoid unnecessary and inadequate use of chemicals when applying IPM. Moreover, we call attention to the importance of avoiding harvest losses, especially for soybean and maize crops. Lost corn cobs from the previous crop season between soybean plants attract mice in the area and therefore are a major trigger for injuries to soybean pods. Thus, reducing harvest losses is the best way to manage the green bridge and mitigate the problem herein discussed.